Transformational leadership, school culture and risk management practices at elementary schools in Malaysia - Karuppiah, Chanthravalli; Foo, Say Fooi; Abdul Hamid, Jamaliah; Abu Samah, Bahaman (IDOSI Publications, 2014)
This study involves a quantitative investigation on risk management practices and its relationship with transformational leadership and school culture. A quantitative study will be conducted at selected primary schools in Malaysia. The selection of the schools will be on random basis covering both urban and rural. The survey will be conducted among school teachers. Basically two quantitative survey instruments will be used in order to collect data for the research: principal transformational leadership, school culture and risk management practices. Responses from individual teachers will be averaged based on each item and factor to create the school-wide data that's needed for this study. The findings from this study will contribute to the body of knowledge in risk management and practices at schools. It provides guidance on skills required by school leaders for effective risk management practices in schools.